PENAKERJA: IMPLEMENTASI PERMENDIKBUD NOMOR 111 TAHUN 2014 TENTANG BIMBINGAN DAN KONSELING PADA PENDIDIKAN DASAR DAN MENENGAH DI SD MUHHAMMADIYAH PK SURAKARTA DAN MIM PK KARTASURA - Marsudi, Saring; Suwarno, Suwarno; Wulandari, Murfiah Dewi; Hastuti, Winda (Universitas Muhammadiyah Surakarta, 2015)
The general objective of this community service activity is facilitating the theoretical and practical BK services in Muhammadiyah Elementary School of Special Program in Surakarta and MIM Kartasura in implementing Permendikbud No. 111 of 2014 in an effort to improve the professionalism of teachers. In particular, the purpose of the community service is to facilitate the understanding the partner schools in Counselling services in the areas of personal, social, learning, and career. The service activities include socialization Permendikbud No. 111 of 2014 concerning guidance and counseling services in primary school, a discussion on the basic concept of guidance and counseling, and workshops on the implementation of guidance and counseling in Muhammadiyah Elementary School of Special Program in Surakarta and MIM Kartasura. Community service activities have received positive responses namely the formation of a formal institution Institute of Guidance and Counseling in each school. These institutions equipped with the personnel in charge, coordinator and teacher who oversees areas: personal, social, learning, and career.